Nitric oxide-mediated dispersal and enhanced antibiotic sensitivity in pseudomonas aeruginosa biofilms from the cystic fibrosis lung. (4th April 2011) - Howlin, R; Cathie, K; Hall-Stoodley, L; Niehaus, L; Connett, G; Legg, J; Daniels, T; Carroll, M; Jefferies, J; Clarke, S C; Stoodley, P; Webb, J; et al.
Abstract : Background and aims: Bacterial biofilms present a major challenge in medicine due to their recalcitrance towards antimicrobials, relative to the same bacteria in a planktonic (free living) state. In cystic fibrosis (CF), bacteria colonise the lungs, establishing chronic and persistent infections which can not be eradicated with conventional antibiotic treatments. The effective treatment of CF patients colonised with the opportunistic pathogen Pseudomonas aeruginosa (PA) present a major therapeutic challenge not adequately addressed using current conventional antibiotic regimes (eg, ceftazadime and tobramycin in combination). We have previously demonstrated that biofilm formation by PA is reversed in vitro by nanomolar, non-toxic concentrations of NO by reduction of biofilm antibiotic tolerance. The aim of this project is to investigate nitric oxide as adjunctive therapy to standard antibiotic regimes in CF. Methods: Biofilms from clinical isolates of PA were cultured ex vivo from sputum obtained from 20 teenagers and young adults with CF undergoing infective exacerbation. Dispersal, using low dose concentrations of the nitric oxide donor sodium nitroprusside (SNP), was calculated using optical density measurements. The effects of tobramycin and ceftazadime alone, and in combination with SNP, were visualised by Live/Dead fluorescent staining and confocal microscopy. Results: The extent of biofilm dispersal was SNP-concentration dependent and could be significantly reduced by the addition of a nitric oxide scavenger. Moreover, biofilm dispersal was accompanied by increased susceptibility of PA to tobramycin and ceftazadime. Preliminary data also demonstrate dispersal and increased antibiotic susceptibility of multi-species biofilms cultured from CF sputum. Conclusions: These data demonstrate that NO-mediated dispersal can augment the antibiotic sensitivity of PA biofilms from clinical isolates and have led to an ongoing NIHR Respiratory Biomedical Unit funded proof-of-principle clinical trial to assess the clinical role of nitric oxide as adjunctive therapy in CF teenagers and young adults colonised with PA (EudraCT 2010-023529-39).